2022
DOI: 10.3390/molecules27217182
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Dental Composite with Ciprofloxacin Loaded Silver Nanoparticles

Abstract: Resin composites have been widely used in dental restoration. However, polymerization shrinkage and resultant bacterial microleakage are major limitations that may lead to secondary caries. To overcome this, a new type of antibacterial resin composite containing ciprofloxacin-loaded silver nanoparticles (CIP-AgNPs) were synthesized. The chemical reduction approach successfully produced CIP-AgNPs, as demonstrated by FTIR, zeta potential, scanning electron microscopy, and ultraviolet-visible (UV-vis) spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Enhanced antibacterial activity was also observed in a previous study in which Ag was doped on ZnO and incorporated into resin composites [ 7 , 41 ]. The greater the concentration of NPs in composite resin, the greater the enhancement in the antibacterial activity observed, which was similar to a previous study [ 7 , 15 ]. When tested for cytotoxicity, less cytotoxicity was observed even at higher concentrations of Se/ZnO NPs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Enhanced antibacterial activity was also observed in a previous study in which Ag was doped on ZnO and incorporated into resin composites [ 7 , 41 ]. The greater the concentration of NPs in composite resin, the greater the enhancement in the antibacterial activity observed, which was similar to a previous study [ 7 , 15 ]. When tested for cytotoxicity, less cytotoxicity was observed even at higher concentrations of Se/ZnO NPs.…”
Section: Discussionsupporting
confidence: 91%
“…The synthesized pristine and Se/ZnO NPs were confirmed by several characterization techniques routinely used [ 15 , 25 , 26 , 27 , 28 ]. The first confirmation was done by UV-Vis spectrophotometry from UV-2800 BMS Biotechnology Medical Services, Madrid, Spain, spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle size was measured to be 24 nm for unloaded liposomes and 67 nm for silymarin-loaded liposomes. The size increase confirmed the drug loading [ 36 , 39 ]. However, zeta potential measurements showed values of −14.8 mV and −17.8 mV.…”
Section: Discussionmentioning
confidence: 58%
“…It was revealed that the SLNPs exhibited spherical morphology and had an average size of 67 nm, as seen in Figure 3 , whereas the BLNPs had an average size of 24 nm. This demonstrated successful loading of silymarin in the liposome [ 36 ].…”
Section: Resultsmentioning
confidence: 99%